1980
DOI: 10.2136/sssaj1980.03615995004400050046x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Coatings on Rice Roots: Morphology and Models of Development

Abstract: Scanning electron microscopy and X‐ray microanalysis were employed to characterize the morphological properties of iron coatings on rice roots at different growth stages. This information is needed for further understanding of the influence of Fe coatings on rice plant development. Rice root coatings are visible about 1 week after flooding as a brownish discoloration which thickens with age of the root. No coating was found on younger parts of major roots near their tips or on young secondary roots which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(128 citation statements)
references
References 0 publications
13
111
0
2
Order By: Relevance
“…The amounts of iron plaque on the root surfaces of rice were approximately 8-10 g kg −1 at Fe0 and 45-48 g kg −1 at Fe50, which fell within the range (the lowest ∼0.15 g kg −1 and the highest ∼59 g kg −1 ) reported for other wetland plants (St-Cyr and Crowder 1989;Hansel et al 2002) and rice (∼25-102 g kg −1 , Chen et al 1980b) in the field. Uptake of nutrient elements and/or metal(loids) can be mediated by the formation of ion plaque on root surfaces of wetland and some terrestrial plants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The amounts of iron plaque on the root surfaces of rice were approximately 8-10 g kg −1 at Fe0 and 45-48 g kg −1 at Fe50, which fell within the range (the lowest ∼0.15 g kg −1 and the highest ∼59 g kg −1 ) reported for other wetland plants (St-Cyr and Crowder 1989;Hansel et al 2002) and rice (∼25-102 g kg −1 , Chen et al 1980b) in the field. Uptake of nutrient elements and/or metal(loids) can be mediated by the formation of ion plaque on root surfaces of wetland and some terrestrial plants.…”
Section: Discussionsupporting
confidence: 74%
“…The ubiquity of iron plaque observed on rice root surfaces has stimulated investigations on the effects of iron plaque on plant elemental uptake. The formation of iron plaque on the root surfaces of rice and other wetland plants is due to the release of oxygen and oxidants in the rhizosphere and the subsequent oxidation of ferrous to ferric iron and the precipitation of iron oxide or hydroxide on the root surface (Armstrong 1967;Chen et al 1980b;Taylor et al 1984). Mineralogical investigations in wetland fields have shown that the composition of iron plaque in Phalaris arundinacea is mainly ferrihydrite (∼63%) with smaller amounts of goethite (32%) and minor amounts of siderite (5%; Hansel et al 2001), or predominately goethite in Juncus bulbosus (Chabbi 1999) and rice (Chen et al 1980a).…”
Section: Introductionmentioning
confidence: 99%
“…An additional complication with rice is that, in the field, roots are usually coated with iron plaque due to the release of oxygen or oxidants into the rhizosphere, which promotes the oxidation of ferrous to ferric iron, the latter being precipitated on the root surface (Bacha and Hossner, 1977;Chen et al, 1980;Liu et al, 2004Liu et al, , 2005. It has been shown that the presence of iron plaque interferes with the conventional PeAs interactions in soil-plant systems (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Different from the bulk soil, wetland plant such as rice release oxygen and oxidants from the root into the rhizosphere, ferrous iron is then oxidized to ferric iron and deposits on root surface forming iron plaque [78]. Iron plaque is an important biogeochemical component in soil-rice systems affecting the uptake of As by rice plant [79,80] (Figure 1).…”
Section: Interactions Of Microorganisms With Iron Oxidesmentioning
confidence: 99%